Results and Performance of the World Bank Group 2021 - Independent Evaluation Group (World Bank, Washington, DC, 2022)
IEG’s Results and Performance of the World Bank Group 2021 report, also known as RAP 2021, assesses the World Bank Group’s performance by analyzing the achievement of project and program objectives through validated ratings. The World Bank’s outcome ratings steadily improved from FY10 onward and increased by an impressive 9 percentage points in FY20. The largest annual increase over the past five years. IFC’s development outcome ratings increased for the first time in 10 years in all the industry groups and MIGA’s continued to increase, as has been the case over the past decade. The RAP 2021 carries out an in-depth analysis of recent trends, for both the World Bank and the International Finance Corporation, to identify possible drivers behind the increase in project outcome ratings. The report also presents a novel analysis to measure the extent to which the World Bank either repeats project designs or introduces novelty to successor projects. This allowed IEG to detect when teams took informed risk and introduced new elements in projects and assess the effect of this behavior on outcome ratings. The report also analyzes the World Bank’s selection of indicators and use of targets to understand how measurement practices affect ratings and performance. Results point to the need to complement project ratings data with associated evidence of outcomes achieved in client countries, which supports the centrality of the outcome orientation agenda.